Graphic statics in the digital age: A critical review of current methods and trends - Mihajlovska, Teodora; Trombeva-Gavriloska, Ana; Cvetkovska, Meri; Dimevska-Sofronievska, Liljana (Građevinski materijali i konstrukcije, 2025)
Graphic statics is a method for analyzing and designing structures based on the geometric representation of equilibrium conditions, where both forces and structural forms are depicted through reciprocal diagrams. This paper presents a comprehensive review of the development, application, and current state of graphic statics, with particular emphasis on its computational and three-dimensional extensions. Although the fundamentals of graphic statics date back to the 18th century, there has been a resurgence in interest in the field throughout the last three decades, primarily due to improvements in digital modeling and visualization tools. The review is structured into three main sections: the historical evolution of graphic statics and its entry into computational domains; an overview of form-finding methods and their integration into design workflows; and the role of graphic statics as a form-finding method in generating spatial, three-dimensional funicular forms. The paper concludes by identifying key research gaps and arguing for further development of graphic statics as a powerful tool for both architectural exploration and structural optimization.